Brain and human body modeling 2020 : computational human models presented at EMBC 2019 and the BRAIN Initiative 2019 Meeting /: computational human models presented at EMBC 2019 and the BRAIN Initiative 2019 Meeting. ([2021]) - IEEE Engineering in Medicine and Biology Society., Annual International Conference., (41st) 2019 (Berlin, Germany); BRAIN Initiative., Annual Investigators Meeting., (5th) 2019 (Washington, DC)
No abstract available